Characteristics of Risk Taking Executives - MacCrimmon, Kenneth R.; Wehrung, Donald A. (Management Science, 1990)
More than 500 top-level business executives were studied to ascertain the validity of common stereotypes of who takes risks and who avoids risks. We began with 13 risk measures based on theoretical grounds, naturally occurring situations, and attitudes. These measures were formed into seven consolidated measures using factor analysis. Data were gathered on numerous socio-economic variables including ones relating to personal, financial, and professional characteristics. When these characteristics were subjected to factor analysis, four main factors emerged. Linear discriminant analysis was used to address the question of whether risk takers can be differentiated from risk averters. The results were surprisingly clearcut. The most successful executives were the biggest risk takers; the most mature executives were the most risk averse.